Adaptive dual‐radio spectrum‐sensing scheme in cognitive radio networks. Issue 14 (19th August 2011) - Wang, Weiwei; Cai, Jun; Alfa, Attahiru S.; Soong, Anthony C.K.; Li, Simin
ABSTRACT: In this paper, a novel spectrum‐sensing scheme, called adaptive dual‐radio spectrum‐sensing scheme (ADRSS), is proposed for cognitive radio networks. In ADRSS, each secondary user (SU) is equipped with a dual radio. During the data transmission, with the received signal‐to‐noise ratio of primary user (PU) signal, the SU transmitter (SUT) and the SU receiver (SUR) are selected adaptively to sense one channel by one radio while communicating with each other by the other one. The sensing results of the SUR are sent to the SUT through feedback channels (e.g., ACK). After that, with the sensing results from the SUT or the SUR, the SUT can decide whether the channel switching should be carried out. The theoretical analysis and simulation results indicate that the normalized channel efficiency, defined as the expected ratio of time duration without interference to PUs in data transmission to the whole frame length, can be improved while satisfying the interference constraint to PUs. After that, an enhanced ADRSS is designed by integrating ADRSS with cooperative spectrum sensing, and the performance of ADRSS under imperfect feedback channel is also discussed. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : In this paper, an adaptive dual‐radio spectrum‐sensing (ADRSS) scheme is proposed for cognitive radio networks. In this scheme, the secondary user, who has a better primary signal quality in the transmission pair, is allowed to do spectrum sensing without interrupting an ongoing data transmission. The theoretical and simulation results demonstrate that the proposed scheme can improve the normalized channel efficiency without introducing severe interference to primary users.